How do changes in suspended sediment concentration alone influence the size of mud flocs under steady turbulent shearing?. (15th April 2018) - Tran, Duc; Kuprenas, Rachel; Strom, Kyle
Abstract: Modeling the size and settling velocity of sediment under the influence of flocculation is crucial for the accurate prediction of mud movement and deposition in sediment transport modeling of environments such as agricultural streams, large coastal rivers, estuaries, river plumes, and turbidity currents. Yet, collecting accurate and high resolution data on mud flocs is difficult. As a result, models that account for the influence of flocculation on mud settling velocity are based on sparse data that often present non-congruent relationship in floc properties with basic influencers of flocculations such as suspended sediment concentration. This study examines the influence of suspended sediment concentration on floc size populations within a turbulent suspension. Specifically, the work investigates: (1) the relationship between the equilibrium floc size and suspended sediment concentration under conditions of steady concentration and turbulent shearing; and (2) the speed at which mature flocs adapt to an unsteady drop in the concentration when turbulent shear is constant. Two sets of experiments were used to investigate the target processes. All work was conducted in laboratory mixing tanks using a floc camera and a newly developed image acquisition method. The new method allows for direct imaging and sizing of flocs within turbulent suspensions of clay in concentrations ranging from 15 to 400 mg/L, so that no transfer of the sample to another settling column or imaging tank is needed. The primary conclusions from the two sets of experiments are: (1) that the equilibrium floc size in an energetic turbulent suspension is linearly and positively related to concentration over the range of C = 50 to 400 mg/L, yet with a smaller-than-expected slope based on previous data and models from low-energy environments; and (2) that floc sizes decrease quickly (with a time lag on the order of 1–15 min) to time-varying decreases in concentration at turbulent shearing of G = 50 s - 1 . Overall the data illustrate that equilibrium floc size is a positive function of concentration, but that the rate of increase is weaker than expected. The data also suggest that approximating the size or settling velocity of some muds with a simple equilibrium model might be appropriate if the time steps of interest are on the order of 10 min or larger. The data also shows the importance of calibrating historic mud settling velocity equations for accurate predictions. Abstract : Highlights: The influence of concentration alone on floc size is quantified. Floc sizes are measured in a turbulent suspension using a new imaging technique. Equilibrium floc size is a positive, but weaker than expected, function of C. Floc sizes adapt quickly to decreases in concentration.